Antioxidant and Anti‐inflammatory Activities of Methanol Extracts of Tremella fuciformis and Its Major Phenolic Acids. Issue 4 (18th February 2014) - Li, Hua; Lee, Hee‐Seok; Kim, Su‐Hwan; Moon, BoKyung; Lee, Chan
Abstract Methanol extract subfractions of the edible white jelly mushroom (Tremella fuciformis), were assessed for the following antioxidant properties: ABTS+ radical scavenging activity, 1, 1‐diphenyl‐2‐picrylhydrazyl (DPPH) radical scavenging activity, and inhibitory activity of human low‐density lipoprotein (LDL) oxidation. Among the subfractions tested, the chloroform subfraction exhibited the strongest antioxidant activity, with the highest total phenolic content (66.31 μg CAE/mg extract) and flavonoids content (5.12 μg QE/mg extract). The ABTS+ radical scavenging activity of the chloroform subfraction was 7.89 μmol trolox/mg extract, which was the highest among all subfractions. This subfraction also showed the highest DPPH radical scavenging activity and inhibitory activity of LDL oxidation. In addition, the chloroform subfraction demonstrated anti‐inflammatory activity through inhibition of nitric oxide production and inducible nitric oxide synthase expression in RAW 264.7 cells. Major phenolic acids from the mushroom extract were identified as 4‐hydroxybenzoic acid (323 mg/kg dry weight of mushroom), gentisic acid (174 mg/kg dry weight of mushroom), and 4‐coumaric acid (30 mg/kg dry weight of mushroom).